PERHITUNGAN TOTAL OIL LOSSES DAN YIELD REFINED BLEACHED DEODORIZED PALM OIL PADA PROSES REFINING UNIT REFINERY: KASUS PADA PALM OIL INDUSTRY DI DUMAI - Pratama, Aditya Putra; Desniorita, Desniorita (Politeknik ATI Padang, 2021)
A palm oil company in Dumai carries out a refining process aimed at converting crude palm oil (CPO) into edible oil. The refining process involves several steps, including gum binding (degumming), bleaching with bleaching earth, and the removal of certain components (deodorization). During the process, oil losses often occur, particularly during the bleaching and deodorization stages. The lost oil is typically discarded along with Spent Bleaching Earth (SBE) and Palm Fatty Acid Distillate (PFAD). Therefore, it is necessary to calculate the total oil losses during the refining process and the yield of RBDPO products, as well as to identify the factors that influence the oil losses and RBDPO yield. Analysis shows that the Total Oil losses in the refining process range from 0.12% to 0.22%, and the yield of RBDPO obtained ranges from 94.7% to 95%. Oil losses in Spent Bleaching Earth (SBE) are directly proportional to BE dosing in the bleaching process. Meanwhile, deodorized oil losses are inversely proportional to the purity of PFAD. The yield of RBDPO is influenced by total oil losses and the FFA content of CPO as raw material. The total oil losses and the FFA content of CPO as raw material are inversely proportional to the RBDPO yield.